PERAN STRATEGIS KUALITAS PRODUK, HARGA DAN LOKASI DALAM MENDORONG KEPUTUSAN PEMBELIAN KONSUMEN PADA BOOTH TEH KOTA DI MOJOKERTO RAYA - Fajar Budiyanto; Rachmad Sholeh; Oktaviani Permatasari; Trijadi Herdajanto (Jurnal Nusa Manajemen, 2026)
This study aims to analyze the influence of product quality, price, and location on consumer purchasing decisions at Teh Kota booths in the Greater Mojokerto area. The study employed a quantitative approach using a survey method involving 137 consumers who had previously purchased Teh Kota products. Data were collected through a questionnaire using a 5-point Likert scale and analyzed using IBM SPSS Statistics 30 through validity, reliability, classical assumption, multiple linear regression, partial, simultaneous, and dominant tests. The results indicate that product quality, price, and location have a positive and significant effect on purchasing decisions, both partially and simultaneously. The dominant test revealed that location is the most influential factor, followed by product quality and price. These findings suggest that accessibility, booth visibility, and proximity to consumers’ daily activities are the primary considerations in purchasing decisions. Therefore, business owners should optimize strategic locations, maintain product quality, and set appropriate prices to enhance consumer purchasing decisions.